Crystalline forms of compounds of formula i and their preparation and use
Patent Information
- Application Number
- CN202280050574.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-23
- Filing Date
- 2022-07-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-07-22
AI Technical Summary
[0004]目前尚无关于上述式I化合物晶型的相关报道,为进一步优化该化合物的成药性、安全性和有效性等,本发明提供了式I化合物的晶型及其制备和应用
[0109] Compared with the prior art, the present invention has the following main advantages:
Smart Images

Figure CN117769550B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medicinal chemistry, and more specifically to the crystal form of compounds of formula I, their preparation, and applications. Background Technology
[0002] The compounds represented by Formula I are hepatitis B virus nucleocapsid inhibitors, developed by Shanghai Zhimeng Pharmaceutical Technology Co., Ltd., and represent a new class of hepatitis B drugs currently in clinical trials. Currently marketed hepatitis B drugs can control hepatitis B virus replication to a limited extent and slow the progression of cirrhosis, but few can cure chronic hepatitis B. Compounds of Formula I improve the functional cure rate of chronic hepatitis B by inhibiting HBV nucleocapsid formation, and preclinical studies have shown that they have good safety and efficacy.
[0003]
[0004] There are currently no reports on the crystal form of the compound of Formula I. In order to further optimize the drug-likeness, safety and efficacy of the compound, this invention provides the crystal form of the compound of Formula I and its preparation and application. Summary of the Invention
[0005] The purpose of this invention is to provide a crystal form of Formula I compound with higher purity and better drug-like properties, as well as its preparation and application.
[0006] In a first aspect, the present invention provides a crystal form of a compound of formula I.
[0007]
[0008] The crystal form is selected from the following group:
[0009] 1) Crystal form A, wherein the XRPD spectrum of crystal form A has three or more 2θ values selected from the following group: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, 22.67±0.2°, 18.269±0.2°, 32.318±0.2°, 14.924±0.2°;
[0010] 2) Crystal form B, wherein the XRPD spectrum of crystal form B has three or more 2θ values selected from the following group: 23.947±0.2°, 15.861±0.2°, 17.109±0.2°, 10.066±0.2°, 18.738±0.2°, 32.151±0.2°, 8.812±0.2°, 4.645±0.2°;
[0011] 3) Crystal form D, wherein the XRPD spectrum of crystal form D has three or more 2θ values selected from the following group: 24.324±0.2°, 26.505±0.2°, 21.737±0.2°, 17.783±0.2°, 16.018±0.2°, 19.383±0.2°, 27.214±0.2°, 13.234±0.2°, 13.446±0.2°, 20.4±0.2°;
[0012] 4) Crystal form E, wherein the XRPD spectrum of crystal form E has three or more 2θ values selected from the following group: 20.115±0.2°, 18.287±0.2°, 10.002±0.2°, 18.969±0.2°, 16.607±0.2°, 9.132±0.2°, 28.238±0.2°, 25.243±0.2°, 23.626±0.2°, 11.745±0.2°, 24.022±0.2°, 12.538±0.2°;
[0013] 5) Crystal form F, wherein the XRPD spectrum of crystal form F has three or more 2θ values selected from the following group: 11.228±0.2°, 18.503±0.2°, 21.753±0.2°, 16.737±0.2°, 20.331±0.2°, 19.21±0.2°, 10.153±0.2°, 22.536±0.2°, 16.05±0.2°, 10.749±0.2°, 20.687±0.2°, 11.851±0.2°, 12.692±0.2°, 9.246±0.2°, 17.255±0.2°;
[0014] 6) Crystal form G, wherein the XRPD spectrum of crystal form G has three or more 2θ values selected from the following group: 18.452±0.2°, 22.004±0.2°, 24.202±0.2°, 26.664±0.2°, 15.905±0.2°, 20.186±0.2°, 23.922±0.2°, 12.411±0.2°, 14.045±0.2°, 18.872±0.2°, 29.075±0.2°, 20.847±0.2°, 28.137±0.2°, 23.682±0.2°, 32.077±0.2°, 30.333±0.2°.
[0015] In another preferred embodiment, the XRPD pattern of crystal form A has six or more 2θ values selected from the group consisting of: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, 22.67±0.2°, 18.269±0.2°, 32.318±0.2°, and 14.924±0.2°.
[0016] In another preferred embodiment, the XRPD pattern of crystal form A has 10 or more 2θ values selected from the group consisting of: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, and 22.67±0.2°. 2°, 18.269±0.2°, 32.318±0.2°, 14.924±0.2°, 18.54±0.2°, 25.687±0.2°, 27.68±0.2°, 9.091±0.2°, 21.275±0.2°, 28.291±0.2°, 27.397±0.2°, 35.136±0.2°, 33.792±0.2°, 23.702±0.2°.
[0017] In another preferred embodiment, the XRPD pattern of crystal form A has 10 or more 2θ values selected from the group consisting of: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, and 22.67±0.2°. 2°, 18.269±0.2°, 32.318±0.2°, 14.924±0.2°, 18.54±0.2°, 25.687±0.2°, 27.68±0.2°, 9.091±0.2°, 21.275±0.2°, 28.291±0.2°, 27.397±0.2°, 35.136±0.2°, 33.792±0.2°, 23.702±0.2° 23.19±0.2°, 27.974±0.2°, 31.068±0.2°, 29.139±0.2°, 31.535±0.2°, 34.775±0.2°, 19.912±0.2°, 36.58±0.2°, 30.187±0.2°, 33.534±0.2°, 16.939±0.2° 16.688±0.2°, 38.988±0.2°, 22.276±0.2°, 34.067±0.2°, 34.54±0.2°, 35.551±0.2°, 8.783±0.2°, 28.632±0.2°, 37.874±0.2°, 30.526±0.2°, 33.098±0.2°.
[0018] In another preferred embodiment, the XRPD pattern of crystal form A has the following 2θ values: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, 22.6 7±0.2°, 18.269±0.2°, 32.318±0.2°, 14.924±0.2°, 18.54±0.2°, 25.687±0.2°, 27.68±0.2°, 9.091±0.2°, 21.275±0.2°, 28.291±0.2°, 27.397±0.2°, 35.136±0.2°, 33.7 92±0.2°, 23.702±0.2°, 23.19±0.2°, 27.974±0.2°, 31.068±0.2°, 29.139±0.2°, 31.535±0.2°, 34.775±0.2°, 19.912±0.2°, 36.58±0.2°, 30.187±0.2°, 33.534±0.2°, 16 0.939±0.2°, 16.688±0.2°, 38.988±0.2°, 22.276±0.2°, 34.067±0.2°, 34.54±0.2°, 35.551±0.2°, 8.783±0.2°, 28.632±0.2°, 37.874±0.2°, 30.526±0.2°, 33.098±0.2°.
[0019] In another preferred embodiment, the XRPD spectrum of crystal form A has the following group of 2θ values: 24.052, 17.967, 17.352, 12.414, 24.399, 26.578, 11.764, 19.16, 16.423, 22.67, 18.269, 32.318, 14.924, 18.54, 25.687, 27.68, 9.091, 21.275, 28.291, 27.397, 35. 136, 33.792, 23.702, 23.19, 27.974, 31.068, 29.139, 31.535, 34.775, 19.912, 36.58, 30.187, 33.534, 16.939, 16.688, 38.988, 22.276, 34.067, 34.54, 35.551, 8.783, 28.632, 37.874, 30.526, 33.098.
[0020] In another preferred embodiment, the XRPD pattern of crystal form A is substantially as follows: Figure 1 As shown.
[0021] In another preferred embodiment, the crystal form A is amorphous.
[0022] In another preferred embodiment, the water content of crystal form A is ≤0.5%, more preferably ≤0.2%, and even more preferably ≤0.1%.
[0023] In another preferred embodiment, the crystal form A has an endothermic peak at 244-248°C.
[0024] In another preferred embodiment, the crystal form A has essentially the following characteristics: Figure 3 The TGA / DSC diagram shown.
[0025] In another preferred embodiment, the purity of crystal form A is ≥99.5%, more preferably ≥99.7%, and even more preferably ≥99.9%.
[0026] In another preferred embodiment, the XRPD pattern of crystal form B has six or more 2θ values selected from the group consisting of: 23.947±0.2°, 15.861±0.2°, 17.109±0.2°, 10.066±0.2°, 18.738±0.2°, 32.151±0.2°, 8.812±0.2°, and 4.645±0.2°.
[0027] In another preferred embodiment, the XRPD spectrum of crystal form B has the following 2θ values: 23.947±0.2°, 15.861±0.2°, 17.109±0.2°, 10.066±0.2°, 18.738±0.2°, 32.151±0.2°, 8.812±0.2°, and 4.645±0.2°.
[0028] In another preferred embodiment, the XRPD spectrum of the crystal form B has the following 2θ values: 23.947, 15.861, 17.109, 10.066, 18.738, 32.151, 8.812, 4.645.
[0029] In another preferred embodiment, the XRPD pattern of crystal form B is substantially as follows: Figure 4 As shown.
[0030] In another preferred embodiment, the crystal form B loses 4.7-8% of its weight before reaching 210°C.
[0031] In another preferred embodiment, crystal form B has an endothermic peak at 150-165°C and another at 245-250°C; and / or
[0032] The crystal form B has an exothermic peak at 182-192℃.
[0033] In another preferred embodiment, the crystal form B has essentially the following characteristics: Figure 5The TGA / DSC diagram shown.
[0034] In another preferred embodiment, the crystal form B is a solvate.
[0035] In another preferred embodiment, the XRPD pattern of the crystal form D has six or more 2θ values selected from the group consisting of: 24.324±0.2°, 26.505±0.2°, 21.737±0.2°, 17.783±0.2°, 16.018±0.2°, 19.383±0.2°, 27.214±0.2°, 13.234±0.2°, 13.446±0.2°, and 20.4±0.2°.
[0036] In another preferred embodiment, the XRPD pattern of the crystal form D has 10 or more 2θ values selected from the group consisting of: 24.324±0.2°, 26.505±0.2°, 21.737±0.2°, 17.783±0.2°, 16.018±0.2°, 19.383±0.2°, 27.214±0.2°, and 13.234±0.2°. 2°, 13.446±0.2°, 20.4±0.2°, 14.049±0.2°, 14.874±0.2°, 24.833±0.2°, 16.882±0.2°, 23.296±0.2°, 28.146±0.2°, 19.888±0.2°, 16.419±0.2°, 32.839±0.2°.
[0037] In another preferred embodiment, the XRPD pattern of crystal form D has 10 or more 2θ values selected from the group consisting of: 24.324±0.2°, 26.505±0.2°, 21.737±0.2°, 17.783±0.2°, 16.018±0.2°, 19.383±0.2°, 27.214±0.2°, 13.234±0.2°, 13.446±0.2°, 20.4±0.2°, 14.049±0.2°, 14.874±0.2°, 24.833±0.2°, 16.882±0.2°, 23.296±0.2°, 28.146±0.2°, and 19.888±0.2°. °, 16.419±0.2°, 32.839±0.2°, 29.031±0.2°, 22.664±0.2°, 10.817±0.2°, 30.426±0.2°, 34.905±0.2°, 36.698±0.2°, 29.52±0.2°, 9.564±0.2°, 25.225±0.2°, 30.041±0.2°, 32.097±0.2°, 35.215±0.2°, 37.977±0.2°, 39.383±0.2°, 36.192±0.2°, 33.768±0.2°, 39.129±0.2°, 12.522±0.2°.
[0038] In another preferred embodiment, the XRPD pattern of crystal form D has the following group of 2θ values: 24.324±0.2°, 26.505±0.2°, 21.737±0.2°, 17.783±0.2°, 16.018±0.2°, 19.383±0.2°, 27.214±0.2°, 13.234±0.2°, 13.446±0.2°, 20.4±0.2°, 14.049±0.2°, 14.874±0.2°, 24.833±0.2°, 16.882±0.2°, 23. 296±0.2°, 28.146±0.2°, 19.888±0.2°, 16.419±0.2°, 32.839±0.2°, 29.031±0.2°, 22.664±0.2°, 10.817±0.2°, 30.426±0.2°, 34.905±0.2°, 36.698±0.2°, 29.52±0.2°, 9.564±0.2°, 25.225±0.2°, 30.041±0.2°, 32.097±0.2°, 35.215±0.2° 37.977±0.2°, 39.383±0.2°, 36.192±0.2°, 33.768±0.2°, 39.129±0.2°, 12.522±0.2°.
[0039] In another preferred embodiment, the XRPD spectrum of the crystal form D has the following group of 2θ values: 24.324, 26.505, 21.737, 17.783, 16.018, 19.383, 27.214, 13.234, 13.446, 20.4, 14.049, 14.874, 24.833, 16.882, 23.296, 28.146, 19. 888, 16.419, 32.839, 29.031, 22.664, 10.817, 30.426, 34.905, 36.698, 29.52, 9.564, 25.225, 30.041, 32.097, 35.215, 37.977, 39.383, 36.192, 33.768, 39.129, 12.522.
[0040] In another preferred embodiment, the XRPD pattern of the crystal form D is substantially as follows: Figure 10 As shown.
[0041] In another preferred embodiment, the crystal form D loses 16.81% of its weight before reaching 180°C.
[0042] In another preferred embodiment, the crystal form D has an endothermic peak at 111-115°C.
[0043] In another preferred embodiment, the crystal form D has an endothermic peak at 243-250°C.
[0044] In another preferred embodiment, the crystal form D has essentially the following characteristics: Figure 11 The TGA / DSC diagram shown.
[0045] In another preferred embodiment, the crystal form D is a solvate.
[0046] In another preferred embodiment, the XRPD pattern of the crystal form E has six or more 2θ values selected from the group consisting of: 20.115±0.2°, 18.287±0.2°, 10.002±0.2°, 18.969±0.2°, 16.607±0.2°, 9.132±0.2°, 28.238±0.2°, 25.243±0.2°, 23.626±0.2°, 11.745±0.2°, 24.022±0.2°, and 12.538±0.2°.
[0047] In another preferred embodiment, the XRPD pattern of the crystal form E has 10 or more 2θ values selected from the group consisting of: 20.115±0.2°, 18.287±0.2°, 10.002±0.2°, 18.969±0.2°, 16.607±0.2°, 9.132±0.2°, 28.238±0.2°, 25.243±0.2°, 23.626±0.2°, 11.745±0.2°, 24.022±0.2°, 12.538±0.2°, 21.701±0.2°, 14.006±0.2°, 30.392±0.2°, 29.151±0.2°, and 27.509±0.2°. 2°, 16.057±0.2°, 21.085±0.2°, 19.39±0.2°, 22.872±0.2°, 22.327±0.2°, 6.984±0.2°, 26.431±0.2°, 12.824±0.2°, 26.802±0.2°, 15.066±0.2°, 33.301±0.2°, 38.968±0.2°, 10.597±0.2°, 31.95±0.2°, 32.261±0.2°, 30.738±0.2°, 33.682±0.2°, 15.721±0.2°, 37.098±0.2°, 25.834±0.2°.
[0048] In another preferred embodiment, the XRPD spectrum of crystal form E has the following group of 2θ values: 20.115±0.2°, 18.287±0.2°, 10.002±0.2°, 18.969±0.2°, 16.607±0.2°, 9.132±0.2°, 28.238±0.2°, 25.243±0.2°, 23.626±0.2°, 11.745±0.2°, 24.022±0.2°, 12.538±0.2°, 21.701±0.2°, 14.006±0.2°, 30.392±0.2°, 29.151±0.2°, 27.509±0.2°, 16 0.057±0.2°, 21.085±0.2°, 19.39±0.2°, 22.872±0.2°, 22.327±0.2°, 6.984±0.2°, 26.431±0.2°, 12.824±0.2°, 26.802±0.2°, 15.066±0.2°, 33.301±0.2°, 38.968±0.2°, 10.597±0.2°, 31.95±0.2°, 32.261±0.2°, 30.738±0.2°, 33.682±0.2°, 15.721±0.2°, 37.098±0.2°, 25.834±0.2°.
[0049] In another preferred embodiment, the XRPD spectrum of crystal form E has the following 2θ values: 20.115, 18.287, 10.002, 18.969, 16.607, 9.132, 28.238, 25.243, 23.626, 11.745, 24.022, 12.538, 21.701, 14.006, 30.392, 29.151, 27 .509, 16.057, 21.085, 19.39, 22.872, 22.327, 6.984, 26.431, 12.824, 26.802, 15.066, 33.301, 38.968, 10.597, 31.95, 32.261, 30.738, 33.682, 15.721, 37.098, 25.834.
[0050] In another preferred embodiment, the XRPD pattern of crystal form E is substantially as follows: Figure 14 As shown.
[0051] In another preferred embodiment, the crystal form E loses 4.69% of its weight before reaching 210°C.
[0052] In another preferred embodiment, the crystal form E has endothermic peaks at 110-130°C and 140-155°C.
[0053] In another preferred embodiment, the crystal form E has an exothermic peak at 170-188°C.
[0054] In another preferred embodiment, the crystal form E has an endothermic peak at 240-250°C.
[0055] In another preferred embodiment, the TGA / DSC plot of the crystal form E is substantially as follows: Figure 15 As shown.
[0056] In another preferred embodiment, the XRPD pattern of the crystal form F has six or more 2θ values selected from the group consisting of: 11.228±0.2°, 18.503±0.2°, 21.753±0.2°, 16.737±0.2°, 20.331±0.2°, 19.21±0.2°, 10.153±0.2°, 22.536±0.2°, 16.05±0.2°, 10.749±0.2°, 20.687±0.2°, 11.851±0.2°, 12.692±0.2°, 9.246±0.2°, and 17.255±0.2°.
[0057] In another preferred embodiment, the XRPD pattern of the crystal form F has 10 or more 2θ values selected from the group consisting of: 11.228±0.2°, 18.503±0.2°, 21.753±0.2°, 16.737±0.2°, 20.331±0.2°, 19.21±0.2°, 10.153±0.2°, 22.536±0.2°, 16.05±0.2°, 10.749±0.2°, 20.687±0.2°, 11.851±0.2°, 12.692±0.2°, 9.246±0.2°, and 17.255±0.2°.
[0058] In another preferred embodiment, the XRPD pattern of the crystal form F has 10 or more 2θ values selected from the group consisting of: 11.228±0.2°, 18.503±0.2°, 21.753±0.2°, 16.737±0.2°, 20.331±0.2°, 19.21±0.2°, 10.153±0.2°, 22.536±0.2°, 16.05±0.2°, 10. 749±0.2°, 20.687±0.2°, 11.851±0.2°, 12.692±0.2°, 9.246±0.2°, 17.255±0.2°, 15.057±0.2°, 23.846±0.2°, 14.252±0.2°, 7.498±0.2°, 5.193±0.2°, 13.804±0.2°, 25.474±0.2°.
[0059] In another preferred embodiment, the XRPD spectrum of crystal form F has the following group of 2θ values: 11.228±0.2°, 18.503±0.2°, 21.753±0.2°, 16.737±0.2°, 20.331±0.2°, 19.21±0.2°, 10.153±0.2°, 22.536±0.2°, 16.05±0.2°, 10.749±0.2°. 2°, 20.687±0.2°, 11.851±0.2°, 12.692±0.2°, 9.246±0.2°, 17.255±0.2°, 15.057±0.2°, 23.846±0.2°, 14.252±0.2°, 7.498±0.2°, 5.193±0.2°, 13.804±0.2°, 25.474±0.2°.
[0060] In another preferred embodiment, the XRPD spectrum of the crystal form F has the following 2θ values: 11.228, 18.503, 21.753, 16.737, 20.331, 19.21, 10.153, 22.536, 16.05, 10.749, 20.687, 11.851, 12.692, 9.246, 17.255, 15.057, 23.846, 14.252, 7.498, 5.193, 13.804, 25.474.
[0061] In another preferred embodiment, the crystal form F exhibits a weight loss of 2.695% before reaching 210°C.
[0062] In another preferred embodiment, the XRPD pattern of the crystal form G has six or more 2θ values selected from the group consisting of: 18.452±0.2°, 22.004±0.2°, 24.202±0.2°, 26.664±0.2°, 15.905±0.2°, 20.186±0.2°, 23.922±0.2°, 12.411±0.2°, 14.045±0.2°, 18.872±0.2°, 29.075±0.2°, 20.847±0.2°, 28.137±0.2°, 23.682±0.2°, 32.077±0.2°, and 30.333±0.2°.
[0063] In another preferred embodiment, the XRPD pattern of the crystal form G has 10 or more 2θ values selected from the group consisting of: 18.452±0.2°, 22.004±0.2°, 24.202±0.2°, 26.664±0.2°, 15.905±0.2°, 20.186±0.2°, 23.922±0.2°, 12.411±0.2°, 14.045±0.2°, 18.872±0.2°, 29.075±0.2°, 20.847±0.2°, 28.137±0.2°, 23.682±0.2°, 32.077±0.2°, and 30.333±0.2°.
[0064] In another preferred embodiment, the XRPD pattern of the crystal form G has 10 or more 2θ values selected from the group consisting of: 18.452±0.2°, 22.004±0.2°, 24.202±0.2°, 26.664±0.2°, 15.905±0.2°, 20.186±0.2°, 23.922±0.2°, 12.411±0.2°, 14.045±0.2°, 18.872±0.2°, 29.075±0.2°, 20.847±0.2°, 28.137±0.2°, 23.682±0.2°, and 32.077±0.2°. 2°, 30.333±0.2°, 13.815±0.2°, 24.935±0.2°, 27.652±0.2°, 21.088±0.2°, 26.177±0.2°, 17.534±0.2°, 30.889±0.2°, 35.293±0.2°, 33.922±0.2°, 29.875±0.2°, 16.334±0.2°, 38.674±0.2°, 38.538±0.2°, 14.587±0.2°, 7.041±0.2°, 10.559±0.2°, 5.489±0.2°.
[0065] In another preferred embodiment, the XRPD spectrum of the crystal form G has the following 2θ values: 18.452±0.2°, 22.004±0.2°, 24.202±0.2°, 26.664±0.2°, 15.905±0.2°, 20.186±0.2°, 23.922±0.2°, 12.411±0.2°, 14.045±0.2°, 18.872±0.2°, 29.075±0.2°, 20.847±0.2°, 28.137±0.2°, 23.682±0.2°, 32.077±0.2°, 30 0.333±0.2°, 13.815±0.2°, 24.935±0.2°, 27.652±0.2°, 21.088±0.2°, 26.177±0.2°, 17.534±0.2°, 30.889±0.2°, 35.293±0.2°, 33.922±0.2°, 29.875±0.2°, 16.334±0.2°, 38.674±0.2°, 38.538±0.2°, 14.587±0.2°, 7.041±0.2°, 10.559±0.2°, 5.489±0.2°.
[0066] In another preferred embodiment, the XRPD spectrum of the crystal form G has the following 2θ values: 18.452, 22.004, 24.202, 26.664, 15.905, 20.186, 23.922, 12.411, 14.045, 18.872, 29.075, 20.847, 28.137, 23.682, 32 .077, 30.333, 13.815, 24.935, 27.652, 21.088, 26.177, 17.534, 30.889, 35.293, 33.922, 29.875, 16.334, 38.674, 38.538, 14.587, 7.041, 10.559, 5.489.
[0067] In another preferred embodiment, the XRPD pattern of the crystal form G is substantially as follows: Figure 19 As shown.
[0068] In another preferred embodiment, the crystal form G has endothermic peaks at 218-222°C and 245-250°C; and / or
[0069] The crystal form G has a sharp exothermic peak at 220-224℃.
[0070] In another preferred embodiment, the TGA / DSC plot of the crystal form G is substantially as follows: Figure 20 As shown.
[0071] In another preferred embodiment, the crystal form G is amorphous.
[0072] A second aspect of the present invention provides a pharmaceutical composition comprising:
[0073] 1) One or more crystal forms as described in the first aspect of the present invention; and
[0074] 2) Pharmaceutically acceptable carriers or excipients.
[0075] A third aspect of the present invention provides the use of the crystal form described in the first aspect of the present invention for preparing a drug against hepatitis B virus.
[0076] In another preferred embodiment, the drug is used to treat hepatitis B virus infection in mammals.
[0077] It should be understood that, within the scope of this invention, the above-described technical features of this invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here. Attached Figure Description
[0078] Figure 1 This is the XRPD pattern of crystal form A obtained in Example 1.
[0079] Figure 2 This is the PLM diagram (200×) for crystal form A.
[0080] Figure 3 This is the TGA / DSC image of crystal form A.
[0081] Figure 4 This is the XRPD pattern of crystal form B.
[0082] Figure 5 This is the TGA / DSC diagram of crystal form B (D220-PS-03-A6).
[0083] Figure 6 This is a comparison image of XRPD before and after heating of crystal form B (D220-PS-03-A6).
[0084] Figure 7 The image shows the H-NMR spectrum of crystal form B (D220-PS-03-A6).
[0085] Figure 8 The image shows the TGA / DSC plot of crystal form B (D220-PS-05-A1).
[0086] Figure 9 The image shows the H-NMR spectrum of crystal form B (D220-PS-05-A1).
[0087] Figure 10 The image shows the XRPD pattern of crystal form D (D220-PS-08-A17).
[0088] Figure 11 The TGA / DSC diagram is for crystal form D (D220-PS-08-A17).
[0089] Figure 12 This is a comparison image of XRPD before and after heating of crystal form D (D220-PS-08-A17).
[0090] Figure 13 The image shows the H-NMR spectrum of crystal form D (D220-PS-08-A17).
[0091] Figure 14 The image shows the XRPD pattern of crystal form E (D220-PS-06-A1).
[0092] Figure 15 The image shows the TGA / DSC plot of crystal form E (D220-PS-06-A1).
[0093] Figure 16 and Figure 17 Comparison of XRPD values (I / II) of crystal form E (D220-PS-06-A1) before and after heating.
[0094] Figure 18 The image shows a comparison of XRPD values for crystal form F (D220-PS-06-A1 AFT130) before and after being placed at room temperature.
[0095] Figure 19 This is the XRPD diagram of crystal form G.
[0096] Figure 20 This is the TGA / DSC diagram of crystal form G.
[0097] Figure 21 TGA image of crystal form F (D220-PS-06-A1 AFT130) transformed into crystal form E at room temperature.
[0098] Figure 22 These are XRPD comparison images of crystal forms A / B / D / E / F / G.
[0099] Figure 23 This is a comparison chart of XRPD results from the A / G suspension competition experiment.
[0100] Figure 24 and Figure 25 This is the XRPD diagram of the solid obtained from the critical water activity experiment at room temperature.
[0101] Figure 26 This is the DVS diagram for crystal form A.
[0102] Figure 27 This is a comparison of XRPD before and after the DVS test for crystal form A.
[0103] Figure 28 This is a comparison chart of XRPD values for the stability of crystal form A over one week.
[0104] Figure 29 This is a comparison chart of XRPD stability of crystal form A over two weeks.
[0105] Figure 30 This is a diagram showing the transformation relationships of the six crystal forms of compound I.
[0106] Figure 31 The image shows the XRPD plot of compound I obtained in Example 3 of WO2017173999 A1. Detailed Implementation
[0107] Through long-term and in-depth research, the inventors obtained a crystal form of Formula I compound with higher purity and superior drug-forming properties through extensive screening and process optimization. Based on this, the inventors completed this invention.
[0108] As used in this article, the term "n or more 2θ values selected from the following group" refers to any positive integer including n and greater than n (e.g., n, n+1, ...), where the upper limit Nup is the number of all 2θ peaks in the group. For example, "1 or more" includes not only the positive integers of the upper limit Nup (1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, ...), but also ranges such as "2 or more", "3 or more", "4 or more", "5 or more", "6 or more", "7 or more", "8 or more", "9 or more", and "10 or more". For example, "3 or more" not only includes the positive integers up to the upper limit Nup of 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, ..., but also includes the ranges of "4 or more", "5 or more", "6 or more", "7 or more", "8 or more", "9 or more", "10 or more".
[0109] Compared with the prior art, the present invention has the following main advantages:
[0110] (1) Compared with the compound disclosed in WO2017173999 A1, the crystal form of the present invention is the most stable crystal form; at the same time, the crystallization and purification methods disclosed in the present invention are lower in cost and more conducive to the operation process of scale-up production.
[0111] (2) Compared with WO2017173999 A1, the present invention obtains a crystal form with high purity, high yield and significantly reduced impurity content by optimizing the process;
[0112] (3) Compared to WO2017173999 A1, the amorphous product obtained there is a risk of crystallization during storage, and its solid-state stability is poor. The crystal form obtained by this invention has higher solid-state stability and is more conducive to long-term storage. The data also show that the crystal form has good chemical stability, produces fewer impurities during storage, and these impurities are statistically significant, resulting in a longer shelf life for the active pharmaceutical ingredient.
[0113] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are by weight.
[0114] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described herein are for illustrative purposes only.
[0115] General testing methods
[0116] X-ray powder diffraction (XRPD)
[0117] X-ray powder diffraction data of the samples were collected under ambient conditions using a Bruker D2 X-ray powder diffractometer with an X-ray emitter power of 300W. The sample stage had no background signal. The step speed was 0.15 s / step, the total number of steps was 1837, the step size was 2θ = 0.02°, the voltage was 30 kV, and the current was 10 mA. A Cu target (Kα) was used in the X-ray tube, with a Kα2 / Kα1 intensity ratio of 0.50.
[0118] High-performance liquid chromatography (HPLC)
[0119] Purity and solubility data of the samples were collected using an Agilent 1260 high-performance liquid chromatograph (equipped with a DAD detector). The test methods are shown in Table A.
[0120] Table A: Summary of HPLC methods for testing sample purity and solubility
[0121]
[0122] Polarizing microscope (PLM)
[0123] Photographs of the samples were collected at room temperature using an Olympus BX53M polarizing microscope.
[0124] Thermogravimetric Analysis (TGA)
[0125] Thermogravimetric data of the samples were collected using a TA Discovery series thermogravimetric analyzer (TGA). A few milligrams of sample were placed in a Tzero aluminum pan and heated from room temperature to 400°C under N2 protection at a flow rate of 25 mL / min and a heating rate of 10°C / min.
[0126] Differential Scanning Calorimeter (DSC)
[0127] Thermal data of the sample were collected using a TA Discovery series differential scanning calorimeter (DSC). A few milligrams of sample were weighed into a Tzero aluminum dish and sealed with a Tzero sealing cap. Heating was carried out under N2 protection at a flow rate of 50 mL / min and a heating rate of 10 °C / min.
[0128] Dynamic Gas Phase Adsorption Analyzer (DVS)
[0129] Hygroscopicity data of the samples were collected using an ADVENTURE series dynamic gas phase adsorption (DVS) system under N2 protection. Sample volume was approximately 30 mg. The test method for non-crystalline samples is as follows:
[0130] 1) Relative humidity increase process: 0%RH to 90%RH, at a rate of 10%RH / stage; 90%RH to 95%RH, at a rate of 5%RH / stage;
[0131] 2) Relative humidity reduction process: from 95%RH to 90%RH, at a rate of 5%RH / stage; from 90%RH to 5%RH, at a rate of 10%RH / stage.
[0132] Hydrogen nuclear magnetic resonance (H-NMR) spectrum
[0133] The 1H NMR spectrum of the sample was collected using an Agilent VNMR 400MR instrument. A few milligrams of sample were dissolved in DMSO-d6 reagent and then analyzed by the instrument.
[0134]
[0135] Raw material preparation example
[0136] Example A-1 Synthesis of compound 32
[0137]
[0138] At room temperature, toluene (303 kg), compound 31 (35 kg), and p-toluenesulfonic acid (7 kg) were added sequentially to a reaction vessel. The mixture was heated to 105–115 °C and stirred to remove water for 1 hour. The temperature was then lowered to 60–80 °C, and compound 24 (28.33 kg) was added to the reaction vessel. The temperature was raised to 110–120 °C, and the mixture was refluxed to remove water for 12 hours. The temperature was then lowered to 78–80 °C, and additional p-toluenesulfonic acid (180 g) and compound 24 (505 g) were added. The mixture was heated and refluxed to remove water for another 7–8 hours. HPLC control showed that compound 31 was completely converted. The reaction system was then cooled to 50–55 °C, methanol (35.4 kg) was added, and the mixture was stirred for 2 hours. After cooling, the mixture was filtered, and the resulting filter cake was washed with a small amount of toluene / methanol solution. After drying, 40.5 kg of compound 32 was obtained, with a yield of 72.5% and an HPLC purity of 98%.
[0139] MS:[M+H] + =551.4 / 553.4
[0140] Example A-2 Synthesis of Compound 33
[0141]
[0142] At room temperature, ethyl acetate (8 L, 44.8 V), compound 32 (178.3 g, 1.0 eq.), triethylamine (80 mL, 0.45 V), and Raney nickel (48 g, 27%) were added to a reaction flask. The reaction system was purged with hydrogen three times and reacted at room temperature for 8 h. HPLC control showed complete conversion of compound 32. The mixture was filtered, and the filtrate was concentrated to give 160.4 g of compound 33. The yield was 95.1%, and the HPLC purity was 98.2%. MS: [M+H] + =521.5 / 523.5
[0143] Example A-3: Resolution of compound 33
[0144]
[0145] 5 g of racemic compound 33 was separated using a chiral column with methanol as the main mobile phase. Chiral separation yielded 1.3 g of compound 34 (ee > 99%) and 1.78 g of compound 34-S.
[0146] Synthesis of Compound 17 in Example A-4
[0147]
[0148] Add 6 L of dichloromethane to the reaction vessel and cool to approximately -10°C. Add triphosgene (BTC) (170.75 g, 0.58 mol). Slowly add a 4.8 L solution of compound 34 (600 g, 1.15 mol) in dichloromethane to the above triphosgene solution in dichloromethane. Stir for 30 minutes. Keeping below -5°C, add a 1.2 L solution of pyridine (273.07 g, 3.45 mol) in dichloromethane, stirring for at least 20 minutes after the addition is complete. Keeping below -5°C, add 0.9 L of ammonia water, continuing the reaction for at least 30 minutes.
[0149] After the reaction was monitored by HPLC, the product was washed twice with water and concentrated. The resulting product was dissolved in ethyl acetate and then slurried with n-heptane. The filter cake was collected, dried, and 590 g of compound 17 was obtained, yield: 90.86%, purity: 98.45%. MS: [M+H] + =563.01 / 565.02
[0150] Synthesis of Compound 9 in Example A-5
[0151]
[0152] Compound 17 (190 g, 0.337 mol) was dissolved in acetonitrile (1.3 L), and PPTS (pyridine p-toluenesulfonate) (42.3 g, 0.168 mol) and NIS (N-iodosuccinimide) (90.88 g, 0.4 mol) were added. After reacting overnight at 56 °C, a large amount of solid precipitated. After passing HPLC analysis, the mixture was cooled to 20-30 °C and washed with 5% sodium sulfite solution. The solid was collected by filtration and washed with MTBE (methyl tert-butyl ether). After drying, 202 g of compound 9 (compound II) was obtained, yield: 86.9%, purity: 98.75%. MS: [M+H] + =689.84 / 691.84
[0153] For more details regarding the preparation of the compounds, please refer to the following application filed on the same day:
[0154] Invention Title: A Method for Preparing a Hepatitis B Virus Nucleocapsid Inhibitor
[0155] Application date: July 23, 2021
[0156] Applicant: Shanghai Zhimeng Pharmaceutical Technology Co., Ltd.
[0157] Crystal form preparation example
[0158] Example 1: Preparation and characterization of crystal form A
[0159]
[0160] Add 25.760 kg of DMSO (dimethyl sulfoxide) to the reactor under nitrogen protection and start stirring. While maintaining below 40°C, add 2.9 kg of compound II to the reactor and continue stirring. Add 0.74 kg of DBU to the same reactor. Add 0.27 kg of copper powder to the same reactor. After the additions are complete, raise the temperature to 70°C and react for at least 8 hours. After confirming complete conversion of compound II, cool the temperature to below 30°C, add 0.3 kg of activated carbon to the reactor, stir for 30 minutes, and then filter to remove the activated carbon and copper powder. Wash the filter cake with a small amount of DMSO. Combine the filtrates and add 32 kg of 10% acetic acid aqueous solution to the filtrate. After the addition is complete, maintain below 40°C and stir for 1 hour, then filter. Wash the filter cake with a small amount of drinking water and collect the filter cake. Pulverize the resulting filter cake with a 4:1 mixture of ethyl acetate and tetrahydrofuran, filter, and wash the filter cake with a small amount of tetrahydrofuran. Transfer the filtrate to the reactor. The resulting solution was washed with 16.4 kg of 10% acetic acid aqueous solution, 15 kg of 1% potassium carbonate aqueous solution, and 15.6 kg of 5% sodium chloride aqueous solution, respectively. The organic compound was dried with anhydrous sodium sulfate and filtered. The filtrate was collected and concentrated under reduced pressure to remove the organic solvent until no solvent flowed out. 6.8 kg of acetone was weighed and evaporated with the solvent until no solvent flowed out. 4.6 kg of acetone was weighed and added to the residue, and the mixture was heated under reflux for 1 hour. The temperature was lowered to 5-10°C. After stirring for 1 hour, the mixture was filtered. The filter cake was washed with a small amount of acetone. The resulting wet solid was dried to a moisture content ≤1%. 1.655 kg of crude compound I was obtained as a grayish-yellow to pale yellow solid powder. The yield was 70.3%, and the purity was 99.68%.
[0161] Add 6.2 kg of acetic acid and 1.655 kg of crude compound I to a reaction flask, and heat to 80 ± 5 °C until dissolved. Filter at a temperature not lower than 50 °C, then cool to 25 °C and filter again. Wash the filter cake with a small amount of water. Dry the resulting wet solid to obtain 1.538 kg of compound I (monopure), as a pale yellow to off-white solid powder, with a yield of 93.1% and a purity of 99.9%.
[0162] Add 2.432 kg of acetone and 1.538 kg of compound I (monopure) to the reaction vessel. Initiate heating to reflux. Maintain reflux with stirring for at least 1 hour. Cool and filter. Wash the filter cake with a small amount of acetone. Dry the resulting wet solid to obtain 1.458 kg of compound I crystal form A, as a white solid powder, yield: 94.8%, purity: 99.90%.
[0163] result
[0164] 1) Regarding solid-state properties, upon repetition, the white solid of compound I obtained by chiral resolution in Example 3 of WO2017173999 A1 was amorphous (for its XRPD results, please refer to the present invention). Figure 31 ).
[0165] Specifically, in Example 3 of WO2017173999 A1, Compound I, a white solid, was amorphous and failed to yield a stable crystalline form, exhibiting poor solid-state stability. Drug substances prepared using this method have uncertainties in solid-state stability, and there is a risk of further crystallization upon prolonged storage. The solubility and bioavailability of the corresponding samples are also uncertain, resulting in poor drug-like properties.
[0166] 2) Regarding chemical purity, the product purity reported in Example 3 of WO2017173999 A1 is only 98.47%. This is significantly lower than the product purity of 99.90% obtained in Example 1 of this invention. Given that the intermediates 3-(4-acetamido-3-nitrophenylethyl)-2-(3-(4-fluorophenyl)-1-(4-bromophenyl)-1H-pyrazol-4-yl)oxazolidin-4-one, 3-(4-amino-3-nitrophenylethyl)-2-(1-(4-bromophenyl)-3-(4-fluorophenyl)-1H-pyrazol-4-yl)oxazolidin-4-one, and 2-(1-(4-bromophenyl)-3-(4-fluorophenyl)-1H-pyrazol-4-yl)-3-(3,4-diaminophenylethyl)oxazolin-4-one were all positive in the AMES test in the last three chemical steps of the synthesis in WO2017173999 A1, there is a potential risk. Residual of these three impurities in the active pharmaceutical ingredient (API) can seriously affect its quality. The crystal form A disclosed in this invention, along with its preparation and purification, effectively avoids the use of related intermediates. At the same time, the purity is generally above 99.5%, and can even reach 99.90%, effectively reducing the residue of various harmful impurities in the active pharmaceutical ingredient.
[0167] Table M-1 shows the test results of crystal form A obtained in Example 1.
[0168] Table M-1
[0169] Appearance off-white powder Moisture content (KF) 0.09% Residue on ignition (ROI) 0.02% <![CDATA[Specific rotation [α] D 20 (c = 0.25, tetrahydrofuran)]]> +50.4° Total impurities 0.10% Enantiomers (HPLC) Not detected Content (HPLC) (based on anhydrous content) 99.3%
[0170] Table M-2 Results of Experiments on Factors Affecting Crystal Form A in Example 1 (High Temperature and High Humidity Conditions)
[0171]
[0172] Table M-3 Results of Experiments on Factors Affecting Crystal Form A in Example 1 (High Temperature and Humidity, Light Conditions)
[0173]
[0174]
[0175] Based on the comparative data from the above experiments on influencing factors, it can be seen that compared to the 98.47% purity of compound I sample obtained in Example 3 of WO2017173999 A1, the initial purity of crystal form A (99.75%) is higher. Furthermore, crystal form A exhibits good chemical stability and good drug-like properties under high temperature and high humidity conditions.
[0176] Figure 1 This is the XRPD pattern of crystal form A obtained in Example 1.
[0177] Table 1-1 summarizes the XRPD data for crystal form A, with the 2θ value error range being ±0.2°.
[0178] Table 1-1 Summary of XRPD data for crystal form A
[0179] 1 8.783 1.90% 13 19.16 15.30% 25 27.68 8.20% 37 33.792 5.20% 2 9.091 7.50% 14 19.912 3.60% 26 27.974 4.50% 38 34.067 2.10% 3 11.764 18.10% 15 21.275 7.10% 27 28.291 6.20% 39 34.54 2.00% 4 12.414 31.50% 16 22.276 2.40% 28 28.632 1.90% 40 34.775 3.80% 5 14.924 10.20% 17 22.67 12.30% 29 29.139 3.80% 41 35.136 5.40% 6 16.423 13.10% 18 23.19 4.50% 30 30.187 3.40% 42 35.551 2.00% 7 16.688 2.70% 19 23.702 5.10% 31 30.526 1.20% 43 36.58 3.50% 8 16.939 2.80% 20 24.052 100.0% 32 31.068 4.30% 44 37.874 1.70% 9 17.352 41.50% 21 24.399 21.80% 33 31.535 3.80% 45 38.988 2.50%
[0180] 11 18.269 11.50% 23 26.578 20.20% 35 33.098 1.00% 12 18.54 8.70% 24 27.397 5.90% 36 33.534 2.90%
[0181] Figure 2 This is the PLM diagram (200×) for crystal form A.
[0182] from Figure 2 It can be seen that crystal form A is in the form of tiny particles.
[0183] Figure 3 This is the TGA / DSC image of crystal form A.
[0184] from Figure 3 It can be seen that the sample had almost no weight loss before decomposition and had a sharp melting peak at 246.2℃ (initial temperature).
[0185] The above results indicate that crystal form A is an amorphous form.
[0186] Example 2: Discussion of Further Crystal Form Screening Results
[0187] Polymorph screening
[0188] Based on the properties of compound I, and considering factors such as solvent type and temperature, a total of 65 crystal form screening experiments were conducted. Methods included antisolvent addition, gas-solid diffusion, gas-liquid diffusion, slow evaporation, polymer induction, stirring at room temperature / 50°C, and slow cooling. Detailed method descriptions are provided below.
[0189] It should be understood that all compounds I used in the following crystal form screening are compounds I prepared by the preparation method shown in this invention.
[0190] Antisolvent addition method
[0191] Weigh approximately 15 mg of compound I sample and add the positive solvent listed in Table 2. Stir at room temperature to obtain a clear stock solution. Dispense the stock solution into 20 mL glass bottles. Under magnetic stirring, gradually add 0.2–0.5 mL of the corresponding antisolvent until a solid appears or the total solvent volume reaches 15.0 mL. The results (Table 1) show that the antisolvent addition method yields crystal form A, crystal form B, a mixture of crystal forms A and B, and a mixture of crystal forms E and A.
[0192] Table 1. Experimental results of antisolvent addition
[0193]
[0194]
[0195] # Clarification was achieved by adding antisolvent at 5℃ or -20℃, and the solid was obtained by evaporation at room temperature.
[0196] Gas-solid diffusion method
[0197] Weigh approximately 12 mg of compound I crystal form A into a 4 mL glass bottle and place it into a 20 mL glass bottle containing 3 mL of volatile solvent. Seal the 20 mL bottle tightly and leave it at room temperature for approximately two weeks. Characterize the resulting solid using XRPD. The results (Table 2) show that crystal forms A and D were obtained via gas-solid diffusion.
[0198] Table 2 Results of gas-solid diffusion experiments
[0199]
[0200] Gas-liquid diffusion method
[0201] Weigh approximately 15 mg of compound I sample into a 4 mL glass bottle, dissolve the sample in the corresponding solvent listed in Table 4, and then transfer the solution to a 20 mL glass bottle containing 4 mL of antisolvent. Seal the 20 mL bottle tightly and leave it at room temperature until a solid precipitates. Characterize the obtained solid using XRPD. The results (Table 3) show that crystal forms A and B were obtained using the gas-liquid diffusion method.
[0202] Table 3 Results of gas-liquid diffusion experiments
[0203]
[0204]
[0205] *: The sample became clear after 21 days, and the solid was obtained by evaporation at room temperature.
[0206] slow evaporation at room temperature
[0207] Weigh approximately 15 mg of compound I sample into a 4 mL glass bottle and add the corresponding solvent from Table 5 to dissolve it completely. Seal the bottle with sealing film and poke 4–6 pinholes, then allow it to slowly evaporate at room temperature. Characterize the final solid by XRPD. The results (Table 4) show that the slow evaporation method at room temperature yields three crystal forms, namely crystal forms A, B, and E.
[0208] Table 4 Results of the slow evaporation experiment at room temperature
[0209]
[0210] Polymer-induced method
[0211] Weigh 8-15 mg of compound I crystal form A into a 4 mL glass bottle and dissolve it in the appropriate solvent. If it cannot be dissolved completely, filter the suspension through a nylon membrane (0.22 μm pore size). Add 1-2 mg of polymer (PVC / PVP 1:1, w / w) to the filtrate. Seal the 4 mL glass bottle with sealing film, leaving 4-6 pinholes in the film, and allow it to evaporate slowly at room temperature. Characterize the final solid by XRPD. The results (Table 5) show that the polymer-induced method only yields crystal form A.
[0212] Table 5 Results of polymer-induced experiments
[0213]
[0214] Room temperature stirring method
[0215] Weigh approximately 15 mg of compound I, crystal form A, into an HPLC vial, add 0.4 mL of the corresponding solvent, and magnetically stir at room temperature to obtain a suspension. After about one week, separate the solid for XRPD characterization. The results (Table 6) show that the room temperature stirring method yielded two crystal forms, crystal forms A and D.
[0216] Table 6 Results of room temperature stirring experiment
[0217]
[0218] 50℃ stirring method
[0219] Weigh approximately 15 mg of compound I, crystal form A, into an HPLC vial, add 0.4 mL of the corresponding solvent, and magnetically stir at 50 °C to obtain a suspension. After 3 days, the solid in the suspension was characterized by XRPD. The results (Table 7) show that the 50 °C stirring method only yielded crystal form A.
[0220] Table 7 Results of stirring experiment at 50℃
[0221]
[0222]
[0223] Slow cooling method
[0224] Weigh approximately 20 mg of compound I crystal form A into a 4 mL glass bottle, add 0.6–0.8 mL of the corresponding solvent, and magnetically stir for 3 hours at 50 °C to obtain a suspension. The suspension was then subjected to membrane filtration (nylon membrane, 0.22 μm pore size). The filtrate was slowly cooled from 50 °C to 5 °C at a cooling rate of 0.1 °C / min. After storing the sample at 5 °C for approximately 2 days, it was transferred to -20 °C to induce crystallization. After storing the sample at -20 °C for approximately 5 days, it was allowed to evaporate at room temperature. Finally, the obtained solid was characterized by XRPD. The experimental results (Table 8) show that crystal forms A, B, and E were obtained through the slow cooling method.
[0225] Table 8 Results of the slow cooling experiment
[0226]
[0227] All samples became clear after being slowly cooled to -20°C, and the solids were obtained by evaporation at room temperature.
[0228] See Table B for the English-Chinese translation of solvent names.
[0229] Table B: Solvent Names (English-Chinese Translation)
[0230]
[0231]
[0232] The results showed that compound I has six crystal forms, including four identified in the crystal form screening experiment (named crystal forms A / B / D / E) and two identified in subsequent crystal form identification (named crystal forms F / G). Among these, there are three amorphous forms (crystal forms A / F / G), one hydrated form (crystal form E), and two solvates (crystal forms B / D). The screening experiment results are summarized in Table 10. The characterization data of the six crystal forms are summarized in Table 11, and the XRPD comparison diagrams are shown below. Figure 22 .
[0233] Table 10 summarizes the results of the crystal form screening experiments for compound I.
[0234]
[0235] Table 11 summarizes the characterization data of the six crystal forms of compound I.
[0236]
[0237]
[0238] Batch number prefix: D220-PS-; []: final temperature;
[0239] @ The sample was a mixture of crystal forms E and F; crystal form F was unstable at room temperature and was not further characterized.
[0240] *: Heat release signal; #: Peak temperature; & Data comes from heating experiments of crystal form E (D220-PS-06-A1).
[0241] Crystal form B
[0242] Figure 4 This is the XRPD pattern of crystal form B.
[0243] Table 1-2 shows the XRPD data for crystal form B, with the 2θ value error ranging from ±0.2°.
[0244] Table 1-2 Summary of XRPD data for crystal form B
[0245] 4.645 1.60% 8.812 2.70% 10.066 13.80% 15.861 17.70% 17.109 16.10% 18.738 13.10% 23.947 100.00% 32.151 4.20%
[0246] Figure 5 This is the TGA / DSC diagram of crystal form B (D220-PS-03-A6).
[0247] from Figure 5 It can be seen that the sample lost 4.9% of its weight before 210℃, had endothermic peaks at 151.1℃ and 245.8℃ (starting point), and had an exothermic peak at 185.3℃ (starting point).
[0248] Figure 6 This is a comparison image of XRPD before and after heating of crystal form B (D220-PS-03-A6).
[0249] from Figure 6 It can be seen that under N2 protection, heating crystal form B (D220-PS-03-A6) to 170℃ and cooling to room temperature transforms it into amorphous form; heating to 210℃ and cooling to room temperature transforms it into crystal form A. This indicates that the first endothermic peak on the DSC is dehydration or desolvation, the exothermic signal is amorphous recrystallization, and the second endothermic peak is the melting point of crystal form A.
[0250] Figure 7 The image shows the H-NMR spectrum of crystal form B (D220-PS-03-A6).
[0251] from Figure 7 It can be seen that the sample (D220-PS-03-A6) contains 4.3% Toluene, which is close to the weight loss of TGA, indicating that crystal form B is a solvate.
[0252] Figure 8 The image shows the TGA / DSC plot of crystal form B (D220-PS-05-A1).
[0253] from Figure 8 It can be seen that the sample lost 7.9% of its weight before 210℃, and there was an endothermic peak at 153.4℃ (the starting point). Based on the weight loss of TGA, it is speculated that it was dehydration or desolvation. There was a sharp endothermic peak at 246.3℃ (the starting point), which is speculated to be melting.
[0254] Figure 9 The image shows the H-NMR spectrum of crystal form B (D220-PS-05-A1).
[0255] from Figure 9 It can be seen that the sample (D220-PS-05-A1) contains 6.5 wt% 1,4-Dioxane, which is close to the weight loss of TGA, indicating that crystal form B is a solvate.
[0256] Based on the above data, crystal form B is a solvate and exhibits isomorphism.
[0257] Crystal form D
[0258] Figure 10 The image shows the XRPD pattern of crystal form D (D220-PS-08-A17).
[0259] Table 1-3 shows the XRPD data for crystal form D, with the 2θ value error ranging from ±0.2°.
[0260] Table 1-3 XRPD data for crystal form D
[0261] 1 9.564 4.40% 14 20.4 15.00% 27 30.426 6.20% 2 10.817 7.20% 15 21.737 44.90% 28 32.097 3.40% 3 12.522 2.10% 16 22.664 8.60% 29 32.839 10.30% 4 13.234 21.40% 17 23.296 12.40% 30 33.768 2.20% 5 13.446 20.20% 18 24.324 100.00% 31 34.905 5.50% 6 14.049 14.10% 19 24.833 12.70% 32 35.215 3.40% 7 14.874 14.10% 20 25.225 3.50% 33 36.192 2.70% 8 16.018 29.30% 21 26.505 91.10% 34 36.698 4.70% 9 16.419 10.50% 22 27.214 25.90% 35 37.977 3.10% 10 16.882 12.60% 23 28.146 12.20% 36 39.129 2.20% 11 17.783 36.10% 24 29.031 9.70% 37 39.383 2.80%
[0262] 13 19.888 11.50% 26 30.041 3.50%
[0263] Figure 11 The TGA / DSC diagram is for crystal form D (D220-PS-08-A17).
[0264] from Figure 11 It can be seen that the sample lost 16.8% of its weight before 180℃, and there was an endothermic peak at 113.1℃ (the starting point). Based on the weight loss of TGA, it is speculated that it was dehydration or desolvation. There was a sharp endothermic peak at 245.9℃ (the starting point), which is speculated to be melting.
[0265] Figure 12 This is a comparison image of XRPD before and after heating of crystal form D (D220-PS-08-A17).
[0266] from Figure 12It can be seen that under N2 protection, heating crystal form D (D220-PS-08-17) to 150℃ and cooling to room temperature transforms it into crystal form A, indicating that crystal form D is a hydrate or solvate.
[0267] Figure 13 The image shows the H-NMR spectrum of crystal form D (D220-PS-08-A17).
[0268] from Figure 13 It can be seen that the sample contains 16.6 wt% CH3COOH, which is similar to the TGA result, indicating that crystal form D is an acetic acid solvate.
[0269] Crystal form E
[0270] Figure 14 The image shows the XRPD pattern of crystal form E (D220-PS-06-A1).
[0271] Table 1-4 shows the XRPD data for crystal form E, with an error range of ±0.2° for the 2θ value.
[0272] Table 1-4 XRPD data for crystal form E
[0273] 1 6.984 3.20% 14 18.969 41.90% 27 27.509 6.40% 2 9.132 20.40% 15 19.39 5.10% 28 28.238 18.80% 3 10.002 59.70% 16 20.115 100.00% 29 29.151 7.10% 4 10.597 1.50% 17 21.085 5.70% 30 30.392 7.80% 5 11.745 13.70% 18 21.701 8.70% 31 30.738 1.20% 6 12.538 11.70% 19 22.327 3.80% 32 31.95 1.30% 7 12.824 2.20% 20 22.872 4.30% 33 32.261 1.30% 8 14.006 8.00% 21 23.626 13.80% 34 33.301 1.80% 9 15.066 1.80% 22 24.022 12.50% 35 33.682 1.00% 10 15.721 0.90% 23 25.243 14.40% 36 37.098 0.80% 11 16.057 5.70% 24 25.834 0.70% 37 38.968 1.60% 12 16.607 33.40% 25 26.431 3.20% 13 18.287 59.90% 26 26.802 2.10%
[0274] Figure 15 The image shows the TGA / DSC plot of crystal form E (D220-PS-06-A1).
[0275] from Figure 15 It can be seen that the sample lost 4.7% of its weight before 210℃, and there were endothermic peaks at 115.1℃ and 145.6℃ (starting point). Based on the weight loss of TGA, it is speculated that it was stepwise dehydration or desolvation. There was an exothermic peak at 172.9℃ (starting point), which is speculated to be amorphous recrystallization. There were endothermic and exothermic peaks at 220.3℃ and 222.3℃ (peak point), respectively, which is speculated to be solid-phase transformation. There was a sharp endothermic peak at 245.4℃ (starting point), which is speculated to be the melting point.
[0276] Figure 16 and Figure 17 Comparison of XRPD values (I / II) of crystal form E (D220-PS-06-A1) before and after heating.
[0277] from Figure 16 and Figure 17 It can be seen that: under N2 protection, when heated to 130℃, part of the sample is transformed into a new crystal form F, indicating that crystal form E is water or a solvate; when heated to 170℃, the sample has weak crystallinity; when heated to 210℃, most of the sample is transformed into crystal form A, and a new diffraction peak is observed and named crystal form G; when heated to 230℃, it is transformed into crystal form A.
[0278] Crystal form F
[0279] Crystal form F can be obtained by dehydration of hydrate crystal form E, but not by solution method. Under N2 protection, new diffraction peaks were observed after heating crystal form E (D220-PS-06-A1) to 130℃ and cooling to room temperature. This new peak was named crystal form F and is presumed to be an amorphous form.
[0280] Crystal form F (D220-PS-06-A1 AFT130) transforms into crystal form E after approximately 3 days at room temperature (18~20℃ / 45~75%RH). Figure 18 The result indicates that the crystal form is unstable at room temperature.
[0281] Figure 21 TGA image of crystal form F (D220-PS-06-A1 AFT130) transformed into crystal form E at room temperature.
[0282] from Figure 21 It can be seen that there is a 2.7% weight loss before 210℃, which indicates that crystal form E is a hydrate.
[0283] Table 1-5 shows the XRPD data for crystal form F, with the 2θ value error ranging from ±0.2°.
[0284] Table 1-5 XRPD data for crystal form F
[0285] 1 5.193 9.10% 12 16.05 40.40% 2 7.498 10.00% 13 16.737 69.00% 3 9.246 26.20% 14 17.255 22.20% 4 10.153 41.10% 15 18.503 96.80% 5 10.749 36.40% 16 19.21 41.70% 6 11.228 100.00% 17 20.331 63.60% 7 11.851 31.70% 18 20.687 35.00% 8 12.692 30.10% 19 21.753 76.70% 9 13.804 8.60% 20 22.536 41.00% 10 14.252 13.00% 21 23.846 14.00% 11 15.057 18.30% 22 25.474 7.50%
[0286] Crystal form G
[0287] Crystal form G can be obtained by solid-phase transformation after dehydration of hydrate crystal form E, and was not obtained by solution method. Under N2 protection, heating hydrate crystal form E to 210℃ and cooling to room temperature yielded the new crystal form G. XRPD results are shown in [Figure number missing]. Figure 19 .
[0288] Table 1-6 shows the XRPD data for crystal form G, with an error range of ±0.2° for the 2θ value.
[0289] Table 1-6 XRPD data for crystal form G
[0290] 1 5.489 1.80% 12 18.872 27.00% 23 27.652 18.40% 2 7.041 3.40% 13 20.186 41.80% 24 28.137 23.70% 3 10.559 3.40% 14 20.847 23.70% 25 29.075 26.20%
[0291] 5 13.815 19.80% 16 22.004 82.00% 27 30.333 20.10% 6 14.045 31.10% 17 23.682 22.90% 28 30.889 6.10% 7 14.587 3.60% 18 23.922 37.50% 29 32.077 21.10% 8 15.905 47.90% 19 24.202 75.90% 30 33.922 5.40% 9 16.334 5.00% 20 24.935 18.90% 31 35.293 5.90% 10 17.534 6.70% 21 26.177 8.00% 32 38.538 4.50% 11 18.452 100.00% 22 26.664 75.90% 33 38.674 5.00%
[0292] Figure 20 This is the TGA / DSC diagram of crystal form G.
[0293] from Figure 20It can be seen that there is almost no weight loss before decomposition, and there are endothermic and exothermic peaks at 220.3℃ and 222.0℃ (peak values), respectively, and a sharp endothermic peak at 246.1℃ (starting point).
[0294] Combination Figure 17 This indicates that crystal form G is amorphous.
[0295] Figure 22 These are XRPD comparison images of crystal forms A / B / D / E / F / G.
[0296] from Figure 22 It can be seen that compound I has six crystal forms, including four found in the crystal form screening experiment (named crystal forms A / B / D / E) and two found in the subsequent crystal form identification (named crystal forms F / G). Among them, there are three amorphous forms (crystal forms A / F / G), one hydrated form (crystal form E), and two solvates (crystal forms B / D).
[0297] Example 3: Study on Crystal Form Relationship
[0298] Crystal-free relationship study
[0299] Three amorphous forms were identified during the crystal form study. Crystal form F was unstable at room temperature and transformed into the hydrated crystal form E upon standing. To investigate the stability relationship among the remaining amorphous forms (crystal form A / G), a suspension competition experiment was conducted using ACN and EtOAc as solvents at room temperature and 60°C. The specific procedure was as follows: Four excess portions of crystal form A were weighed into four HPLC vials. Two vials were added with 0.5 mL of ACN, and the other two with 0.5 mL of EtOAc. The vials were then magnetically stirred at room temperature and 60°C for approximately 2 hours, respectively. The solutions were filtered through a preheated nylon membrane (0.22 μm pore size) to obtain saturated solutions. Approximately 4 mg each of compound I (amorphous forms A and G) were added to the saturated filtrate. The solution was then magnetically stirred at room temperature or 60°C for approximately 2 days. The solids were then separated by centrifugation for XRPD analysis.
[0300] The results (Table 1-7) show that the solids obtained in both solvents at room temperature and 60℃ are of crystal form A. Combined with the fact that crystal form G reverts to crystal form A upon recrystallization after melting, this indicates that crystal form A is thermodynamically more stable than crystal form G. XRPD results are shown in [Table 1-7]. Figure 23 .
[0301] Table 1-7 Competitive results of Compound I in crystal-free A / G suspension at room temperature and 60℃
[0302]
[0303] Key water activity study
[0304] Studies on the relationship between crystal forms showed that compound I is most stable in crystal form A at room temperature. Therefore, crystal form A and hydrate crystal form E were selected for key water activity studies. Specifically, the target water activity (a) was prepared at room temperature. w Prepare a mixed solvent of Acetone / H2O (0 / 0.2 / 0.4 / 0.6 / 0.8 / 1.0) for later use. The water activity of the system corresponding to the volume ratio of Acetone / H2O is shown in Table 1-8. Weigh ~20 mg of crystal form A into the corresponding solvent and stir at room temperature for ~2 hours to obtain a suspension. Filter the suspension through a nylon membrane (pore size 0.22 μm). Weigh ~4 mg of hydrate crystal form E and compound I amorphous crystal form A into HPLC vials, add the above filtrate accordingly, and stir at room temperature for 3-13 days to collect XRPD data.
[0305] Experimental results (Tables 1-8 and 8) Figure 24 / Figure 25 The data shows that water activity (a) w When the water activity is 0–0.8, the obtained solid is compound I in its amorphous form A; when the water activity is 1.0, the obtained solid is the hydrate crystal form E. This indicates that at room temperature, compound I in its amorphous form A is more stable when the water activity is 0–0.8, and hydrate crystal form E is more stable when the water activity is 1.0. The key water activity for compound I in its amorphous form A and hydrate crystal form E is 0.8–1.0.
[0306] Table 1-8 Results of room temperature key water activity experiments for compound I in its amorphous form A and hydrated form E
[0307]
[0308] Example 4: Drug Performance Study
[0309] hygroscopic
[0310] The hygroscopicity of compound I (amorphous form A) was evaluated using DVS at 25°C. Prior to the evaluation, compound I (amorphous form A) was equilibrated under 0% RH conditions to remove water or solvent adsorbed on the surface.
[0311] Depend on Figure 26 It can be seen that compound I, amorphous form A, increased in weight by 0.14% at 80% RH, indicating that the sample is almost non-hygroscopic and the crystal form of the sample remained unchanged after the test. Figure 27 This indicates that it has good crystal stability.
[0312] Solid-state stability
[0313] To evaluate the solid-state stability of the preferred crystal form (compound I without crystal form A), ~20 mg of sample was weighed into an HPLC vial and placed open under three conditions: 1) 25 °C / 60% RH, 2) 40 °C / 75% RH, and 3) 60 °C. Purity tests (HPLC) and crystal form determination (XRPD) were performed on the starting sample, and samples stored for one and two weeks.
[0314] The results showed that crystal form A remained unchanged after one and two weeks of storage under the selected conditions. Figure 28 and Figure 29 The purity did not change significantly (Table 1-9), indicating that crystal form A has good solid-state stability.
[0315] Table 1-9 Summary of Two-Week Stability Data for Crystal Form A
[0316]
[0317] The results show:
[0318] 1) Compound I has almost no moisture absorption in its crystal form A, and its crystal form remains unchanged before and after the DVS test, proving that it has good crystal form stability;
[0319] 2) After being left exposed at 25℃ / 60%RH, 40℃ / 75%RH and 60℃ for two weeks, crystal form A showed no significant changes in crystal form and purity, exhibiting good solid-state stability.
[0320] Solubility
[0321] At room temperature, the approximate solubility of compound I, crystal form A (D220-PS-01-A), in the following 21 solvents was tested. Specifically, ~2 mg of starting material was weighed into an HPLC vial, and solvents listed in the table below were added sequentially (50 / 50 / 200 / 700 μL) until the solid was completely dissolved or the total volume reached 1.0 mL. The obtained data are summarized in Table 1-10.
[0322] Table 1-10 Approximate solubility of compound I, crystal form A, at room temperature
[0323]
[0324]
[0325] Compound I, crystal form A, has low solubility in water but is readily soluble in DMSO, DMF, THF, and acetic acid. Therefore, the purification and recrystallization process for crystal form A is carried out in acetic acid. Compound I, crystal form A, has moderate solubility in acetone, so further purification by slurrying in acetone is chosen to remove structurally similar impurities and related intermediates.
[0326] in conclusion
[0327] A series of crystal form screening experiments on compound I revealed six crystal forms, including three amorphous forms (crystal forms A / F / G), one hydrate crystal form E, and two solvates (crystal forms B / D). The relationship between the amorphous forms was investigated through ripening / heating and suspension competition. The results showed that amorphous form A of compound I was the most stable at room temperature (~18℃) / 60℃. The stability relationship between amorphous form A and hydrate crystal form E of compound I was studied at different water activities. The results showed that at room temperature, amorphous form A of compound I was more stable with a water activity of 0–0.8; while at a water activity of 1.0, hydrate crystal form E was more stable, indicating that the critical water activity for amorphous form A and hydrate crystal form E of compound I is 0.8–1.0. Hygroscopicity assessment of compound I without crystal form A showed that crystal form A is almost non-hygroscopic, and the crystal form remained unchanged before and after DVS testing. Meanwhile, solid-state stability assessment of compound I without crystal form A showed that after being left open for two weeks at 25℃ / 60%RH, 40℃ / 75%RH and 60℃, there were no significant changes in crystal form and purity, demonstrating good solid-state stability.
[0328] Crystal forms F and G were not obtained from the solution method. Crystal form F transformed into hydrate crystal form E after being placed at room temperature (18–20 °C, 45%–75% RH) for 3 days, indicating instability at room temperature. Crystal form G could be converted into crystal form A upon recrystallization after melting. A suspension competition test was conducted on crystal forms A and G. The results showed that crystal form G could be converted into crystal form A in both ACN and EtOAc at room temperature and 60 °C, indicating that crystal form A is thermodynamically more stable than crystal form G.
[0329] The interconversion relationships between different crystal forms can be referenced. Figure 30 The conditions are explained in Table 1-11.
[0330] Table 1-11
[0331]
[0332]
[0333] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by the appended claims.
Claims
1. A crystal form of a compound of formula I, characterized in that, Equation I The crystal form is crystal form A, and the XRPD spectrum of crystal form A has six or more 2θ values selected from the following group: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, 22.67±0.2°, 18.269±0.2°, 32.318±0.2°, and 14.924±0.2°.
2. The crystal form as described in claim 1, characterized in that, The XRPD pattern of crystal form A has the following 2θ values: 24.052±0.2°, 17.967±0.2°, 17.352±0.2°, 12.414±0.2°, 24.399±0.2°, 26.578±0.2°, 11.764±0.2°, 19.16±0.2°, 16.423±0.2°, 22.67±0.2°. 18.269±0.2°, 32.318±0.2°, 14.924±0.2°, 18.54±0.2°, 25.687±0.2°, 27.68±0.2°, 9.091±0.2°, 21.275±0.2°, 28.291±0.2°, 27.397±0.2°, 35.136±0.2°, 33.792±0 0.2°, 23.702±0.2°, 23.19±0.2°, 27.974±0.2°, 31.068±0.2°, 29.139±0.2°, 31.535±0.2°, 34.775±0.2°, 19.912±0.2°, 36.58±0.2°, 30.187±0.2°, 33.534±0.2°, 16.9 39±0.2°, 16.688±0.2°, 38.988±0.2°, 22.276±0.2°, 34.067±0.2°, 34.54±0.2°, 35.551±0.2°, 8.783±0.2°, 28.632±0.2°, 37.874±0.2°, 30.526±0.2°, 33.098±0.2°.
3. The crystal form as described in claim 1, characterized in that, The XRPD spectrum of crystal form A has the following 2θ values: 24.052, 17.967, 17.352, 12.414, 24.399, 26.578, 11.764, 19.16, 16.423, 22.67, 18.269, 32.318, 14.924, 18.54, 25.687, 27.68, 9.091, 21.275, 28.291, 27.397, 35.
136. 33.792, 23.702, 23.19, 27.974, 31.068, 29.139, 31.535, 34.775, 19.912, 36.58, 30.187, 33.534, 16.939, 16.688, 38.988, 22.276, 34.067, 34.54, 35.551, 8.783, 28.632, 37.874, 30.526, 33.
098.
4. The crystal form as described in claim 1, characterized in that, The XRPD pattern of crystal form A is basically shown in Figure 1.
5. The crystal form as described in claim 1, characterized in that, Crystal form A is amorphous.
6. The crystal form as described in claim 1, characterized in that, The crystal form A has a TGA / DSC diagram as shown in Figure 3.
7. The crystal form as described in claim 1, characterized in that, The purity of crystal form A is ≥99.7%.
8. A pharmaceutical composition, characterized in that, Include: 1) The crystal form as described in claim 1; and 2) Pharmaceutically acceptable carrier.
9. Use of the crystal form according to claim 1, characterized in that, Drugs used to prepare anti-hepatitis B virus.
10. The use as described in claim 9, characterized in that, The drug is used to treat hepatitis B virus infection in mammals.
Citation Information
Patent Citations
Pyrazole-oxazolidinone compound for Anti-hepatitis b virus
WO2017173999A1
Pyrazole-oxazolidinone compound for anti-hepatitis b virus
CN109311865A
5-alkyl-2-pyrazole-oxazolidine-4-ketone derivative and application thereof
CN114685473A
Crystal form of compound of formula I and preparation and application thereof
CN115677680A